The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1016/s0893-133x(01)00345-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Studies of the Acute Effects of (+)-3,4-Methylenedioxymethamphetamine on Locomotor Activity, Role of 5-HT1B/1D and 5-HT2 Receptors

Abstract: The role of serotonin 5-HT 2 receptors (5-HT 2 R) in the hyperactivity induced by ( ϩ )-3,4-methylenedioxymethamphetamine (( ϩ )-MDMA; 3 mg/kg) was investigated. Hyperactivity induced by ( ϩ )-MDMA was robustly potentiated by the 5-HT 2B/2C R antagonist SB 206553 (1.0, 2.0, and 4.0 mg/kg). Administration of the 5-HT 1B/1D R antagonist GR 127935 (2.5 mg/kg) or the 5-HT 2A R antagonist M100907 (1.0 mg/kg) partially suppressed the potentiated hyperactivity seen following SB 206553 plus ( ϩ )-MDMA; a blockade t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
93
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 47 publications
17
93
2
Order By: Relevance
“…Consistent with previous reports (Geyer et al 1987), we observed that animals spent more time (>40%) in central than peripheral regions of the chamber following administration of 2 mg/kg (+)-amphetamine. By contrast, several studies from different laboratories have reported observing more peripheral than central activity following (+)-MDMA administration (McCreary et al 1999;Bankson and Cunningham 2002;Gold et al 1988;Callaway et al 1990). In the present experiments, however, locomotor activity was nearly evenly distributed between the central and peripheral areas of the chamber following administration of 5 mg/kg (±)-MDMA.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with previous reports (Geyer et al 1987), we observed that animals spent more time (>40%) in central than peripheral regions of the chamber following administration of 2 mg/kg (+)-amphetamine. By contrast, several studies from different laboratories have reported observing more peripheral than central activity following (+)-MDMA administration (McCreary et al 1999;Bankson and Cunningham 2002;Gold et al 1988;Callaway et al 1990). In the present experiments, however, locomotor activity was nearly evenly distributed between the central and peripheral areas of the chamber following administration of 5 mg/kg (±)-MDMA.…”
Section: Discussionmentioning
confidence: 92%
“…MDMA releases dopamine both directly and indirectly through 5-HT release (Callaway et al 1990;Koch and Galloway 1997;Schmidt et al 1992;Yamamoto and Spanos 1988). Both 5-HT 1B and 5-HT 2 receptors can influence the MDMA locomotor response, although both stimulatory and inhibitory effects have been reported (Bankson and Cunningham 2002;Kehne et al 1996;McCreary et al 1999;Schmidt et al 1992). Estrogen enhances basal, stimulated, and stimulant-induced dopamine release as well as both dopamine and serotonin receptors (see reviews by Becker 1999;Cyr et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms could contribute to this enhanced response including greater changes in dopamine signaling, upregulation of serotonin receptors like that occurring after other manipulations that deplete serotonin, or some adaptation that is specific for MDMA (Dringenberg et al 1995;Gately et al 1985;Nestler 2004). The augmented response in females could reflect a sex-specific receptor upregulation facilitated by estrogen-facilitated 5-HT 2 receptor synthesis (Bankson and Cunningham 2002;Cyr et al 2002;Reneman et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several studies have excluded the possibility that nonspecific behavioral changes, such as hyperlocomotion and even sedation, may account for the hypophagic responses to 5-HT 1B , 5-HT 2A , 5-HT 2B , or 5-HT 2C receptor agonists ( Kitchener and Dourish, 1994; Lee and Simansky, 1997;Hewitt et al, 2002;Clifton et al, 2000Clifton et al, , 2003. The fact that 5-HT 2C receptors may contribute to MDMA-induced hyperlocomotion has been questioned in one study using rats (Bankson and Cunningham, 2002). This investigation reported that SB206553, a 5-HT 2C receptor antagonist, enhanced the motor effects of MDMA in the rat (Bankson and Cunningham, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that 5-HT 2C receptors may contribute to MDMA-induced hyperlocomotion has been questioned in one study using rats (Bankson and Cunningham, 2002). This investigation reported that SB206553, a 5-HT 2C receptor antagonist, enhanced the motor effects of MDMA in the rat (Bankson and Cunningham, 2002). Such a discrepancy may likely be due to dose-or species-specific differences since an acute administration of 3.3 mg/kg MDMA did not stimulate locomotion in mice (Scearce-Levie et al, 1999), but did in rats ( Bankson and Cunningham, 2002).…”
Section: Discussionmentioning
confidence: 99%